'Fuck It, Shit Happens (FISH)': a social generations approach to understanding young people's imaginings of life after school in 2016–2017. (2nd January 2020) - Alexander, Patrick; Loewenthal, John; Butt, Graham
ABSTRACT: This article uses a social generations approach to explore the lives of young people transitioning to life after schooling. Drawing on ethnographic research in England during the geopolitical uncertainty of 2016–2017, we track the trajectories and narratives of six individuals. The research begins with final year pupils in schools talking about their futures, during and after their A-Level exams. We then follow these individuals on routes to Higher Education and employment, exploring how they are socialised into imaginings of the future and/or struggle to inhabit these futures. A deeply ingrained, modernist, neoliberal reckoning of future time is normalised through experiences of schooling. However, this logic is troubled profoundly in the transition to life after school. Young people's experiences in an unpredictable present run in stark contrast to the ordered trajectory of future action they have been socialised to expect. Amidst this uncertainty, ambivalence towards shaping the future ('Fuck It, Shit Happens') can in some ways feel like the most agentic stance to take. Furlong et al.'s (2011) social generations approach to understanding youth transitions reveals how we must critique the very concept of 'the future' if we are to understand the reality of youth transitions in the present.